2018
DOI: 10.1039/c7gc03026f
|View full text |Cite
|
Sign up to set email alerts
|

A lignin-epoxy resin derived from biomass as an alternative to formaldehyde-based wood adhesives

Abstract: Wood products are extensively used to make furniture items and construction materials; however, the majority contain formaldehyde-based adhesives that raise serious health concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(120 citation statements)
references
References 41 publications
5
113
1
Order By: Relevance
“…122 In this study, kraft lignin and glycerol diglycidyl ether were combined to prepare an epoxy resin, and the viability for scale up was assessed. Interestingly, Li et al 122 tested the effect of lignin particle size on resin properties and found that by decreasing the particle size they were able to increase the lignin content in the formulation. Although not directly focusing on lignin particles, these findings illustrate the advantages of using lignin in the sub-micrometer range.…”
Section: Adhesivesmentioning
confidence: 99%
“…122 In this study, kraft lignin and glycerol diglycidyl ether were combined to prepare an epoxy resin, and the viability for scale up was assessed. Interestingly, Li et al 122 tested the effect of lignin particle size on resin properties and found that by decreasing the particle size they were able to increase the lignin content in the formulation. Although not directly focusing on lignin particles, these findings illustrate the advantages of using lignin in the sub-micrometer range.…”
Section: Adhesivesmentioning
confidence: 99%
“…26 In addition, lignins of various sources are intensively studied as vanillin substitutes to be used as environmentally benign antioxidants. 27 Very recently, we reported differences in antioxidant capacity of technical kra versus organosolv-derived lignins studied via DPPH assay. 28 In case of polyol manufacturing, lignin has been investigated for long (starting with Glasser et al y years ago 29 ) as an interesting substitute for fossil-based polyols due to its high concentration of aliphatic and phenolic hydroxy groups.…”
Section: Introductionmentioning
confidence: 99%
“…To further elucidate the strengthening effect of the D‐PU elastomer on the SP matrix, the morphological analysis of the plywood fracture surface is tested by SEM measurement to provide an indication for the situation of adhesion failure. In plywood production, the adhesion process typically includes the resin penetration and curing steps to form adhesion “nails” for mechanical interlocking between the veneer layers . Therefore, for a protein‐based wood resin with excellent performance, an adhesive layer design with a suitable toughness is required to form more adhesion “nails” to obtain strong adhesion within the plywood composites.…”
Section: Resultsmentioning
confidence: 99%
“…Adhesive materials with excellent load‐bearing capability, such as urea formaldehyde, phenol formaldehyde, epoxy resin, and isocyanates, have promising potential for engineered wood products with the structural purpose . In recent years, the increasingly stringent application standards and rapid depletion of nonrenewable fossil resources have aroused a growing interest regarding developing superior bio‐based eco‐friendly resin without formaldehyde emission .…”
Section: Introductionmentioning
confidence: 99%